2005
DOI: 10.1515/ijamh.2005.17.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Have you been sexually harassed in school? What female high school students regard as harassment

Abstract: The aim of the study was to explore what behaviors experienced from peers and school staff at school are acknowledged as sexual harassment, and perceived as problematic, by female high school students, and what other factors may be relevant. Analyses were performed of responses (to 540 questionnaires) in an anonymous self-report mail survey from a random sample of female Swedish high-school students (59% response rate). Exposure to relevant behaviors, of varying levels of severity, alone, does not explain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In our study, we do not know the degree to which girls' reports corresponded to the actual incidence of sexist events. A few prior studies indicate that adolescent girls (Terrance et al, 2004;Witkowska & Gådin, 2005) and women (Bergman, Langhout, Palmieri, Cortina, & Fitzgerald, 2002;Knapp, Faley, Ekeberg, & Dubois, 1997) tend to underestimate the amount of sexual harassment and other forms of sexism targeted at them (viz. the personal/group discrimination discrepancy; Crosby, 1984).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we do not know the degree to which girls' reports corresponded to the actual incidence of sexist events. A few prior studies indicate that adolescent girls (Terrance et al, 2004;Witkowska & Gådin, 2005) and women (Bergman, Langhout, Palmieri, Cortina, & Fitzgerald, 2002;Knapp, Faley, Ekeberg, & Dubois, 1997) tend to underestimate the amount of sexual harassment and other forms of sexism targeted at them (viz. the personal/group discrimination discrepancy; Crosby, 1984).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Yet, although gender-stereotyped beliefs reflect (and perpetuate) gender inequities, few studies have directly examined girls' perceptions of those gender inequities. The existing research suggests that girls often tolerate and/or do not recognize sexual harassment when it occurs (Terrance, Logan, & Peters, 2004;Witkowska & Gådin, 2005). Studies also indicate that girls' experiences with sexual harassment increase with age during adolescence (McMaster, Connolly, Pepler, & Craig, 2002;Pepler et al, 2006).…”
mentioning
confidence: 99%
“…Sexual harassment is a common problem in schools, and therefore often normalised by students [1]. According to the Swedish Discrimination Act [2], sexual harassment refers to actions of a sexual nature that violate someone’s dignity, and is classified as a form of discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in the current research study, we asked participants to report how often they had experienced sexual harassment and STEM-related gender bias after broadly describing each of these forms of discrimination. Past research among adolescent girls found that labeling sexual harassment explicitly may lead to underreporting (Witkowska & Gådin, 2005). This may happen because women do not want to view or label themselves as a victim (Crosby, 1984).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%